1965
DOI: 10.1084/jem.121.6.901
|View full text |Cite
|
Sign up to set email alerts
|

The Origin of the Cells in the Efferent Lymph From a Single Lymph Node

Abstract: The popliteal nodes of sheep were perfused continuously for over 100 hours with a solution containing 3H-thymidine. The labelling pattern of the lymphocytes in the efferent lymph from the perfused nodes showed that under normal conditions not more than 4 per cent of these lymphocytes were actually produced in the node. The transitional cells, large lymphocytes and cells of the plasma cell series which appeared in the lymph following antigenic stimulation of the node were all produced in the node.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
82
1

Year Published

1972
1972
2015
2015

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 200 publications
(86 citation statements)
references
References 8 publications
2
82
1
Order By: Relevance
“…There is a very large traffic of cells through peripheral lymph nodes such as the popliteal node in the sheep (Hall and Morris, 1965) and it would be expected that the very large mass of mesenteric lymph nodes would constitute a major site of lymphocyte recirculation from the blood to the lymph. The lack of any effect of mesenteric lymphadenectomy on the cell output from the intestinal lymph must therefore be due either to the fact that lymphocytes do not recirculate through the mesenteric lymph nodes of the sheep to any extent, or that many of the cells that reach the mesenteric nodes in the lymph frorn the intestines do not leave them in the efferent lymph -they must either die in the node or enter the blood stream directly from within the node.…”
Section: Discussionmentioning
confidence: 99%
“…There is a very large traffic of cells through peripheral lymph nodes such as the popliteal node in the sheep (Hall and Morris, 1965) and it would be expected that the very large mass of mesenteric lymph nodes would constitute a major site of lymphocyte recirculation from the blood to the lymph. The lack of any effect of mesenteric lymphadenectomy on the cell output from the intestinal lymph must therefore be due either to the fact that lymphocytes do not recirculate through the mesenteric lymph nodes of the sheep to any extent, or that many of the cells that reach the mesenteric nodes in the lymph frorn the intestines do not leave them in the efferent lymph -they must either die in the node or enter the blood stream directly from within the node.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, cell concentrations range from 200 to 1000 cells/µL in prenodal sheep's lymph and 100 cells/µL in prenodal rabbit's lymph [127,128] . It was found that approximately 1 × 10 6 cells/h (1.7 × 10 4 cells/min) go through a single prenodal (afferent) sheep's lymphatic [129,130] . According to our data, the cell concentration in rat mesenteric prenodal lymphatics is larger.…”
Section: Study Of Microlymphatic Dynamicsmentioning
confidence: 99%
“…Studies in sheep, a model that permits the long-term monitoring of efferent lymph, have defined several phases of the cell output in the efferent lymph after Ag stimulation (3)(4)(5)(6). In the first 24 h after stimulation, there is no significant change or a slight decrement in the cell output.…”
mentioning
confidence: 99%